The basic psychological needs in physical education scale in Filipino - Cagas, Jonathan (2013)
The Basic Psychological Needs in Physical Education Scale (BPNPE Scale: Vlachopoulos, Katarzi, & Kontou, 2011) is a short instrument grounded in Self-Determination Theory (Ryan & Deci, 2000; 2002), designed to measure fulfillment of students’ basic needs for competence, autonomy, and relatedness in physical education context. The Greek version of this instrument has been reported to have adequate factor structure and strong internal reliability. Instruments developed in other culture need to be examined using a sample from the target culture in order to establish its cultural utility.